Answer:
Step-by-step explanation:
y + 4 = -6(x - 7)
y + 4 = -6x + 42
y = -6x + 38
Answer:
A
Step-by-step explanation:
6ft plus 1 3/4 is 7 3/4
Sorry for minimum explanation but I hope it helped!
Answer:
20,9
Step-by-step explanation:
this is how I did=x=1st, y=2nd; x=4y-16 and x+y=29; thus 4y-16+y=29; 5y-16=29; 5y=45; y=45/5=9, once you know y=9, put in equation, 4y-16=×, (4*9)-16=x, 36-16=x, 20=x
I believe what your asking is just multiplying it together so 5p(p-3) would be 5p2-15p. the p2 is p squared or a little 2 on top of the p. Hope I helped!